2011
DOI: 10.1002/jmri.22704
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of coronary artery wall thickening with age in healthy subjects using high resolution MRI with beat‐to‐beat respiratory motion correction

Abstract: Purpose: To demonstrate coronary artery wall thickening with age in a small healthy cohort using a highly efficient, reliable, and reproducible high-resolution MR technique. Materials and Methods:A 3D cross-sectional MR vessel wall images (0.7 Â 0.7 Â 3 mm resolution) with retrospective beat-to-beat respiratory motion correction (B2B-RMC) were obtained in the proximal right coronary artery of 21 healthy subjects (age, 22-62 years) with no known cardiovascular disease. Lumen and outer wall (lumen þ vessel wall)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…A recent study in a small cohort of healthy volunteers using black‐blood prepared 3D spiral imaging and a highly efficient image based method of respiratory motion compensation has also shown increasing coronary wall thickness with age . This is possibly a precursor of atherosclerosis or it may be part of the normal aging process, or these may be one and the same thing, but the rate of increase in wall thickness observed (0.09 mm per decade) is similar to that observed in autopsy studies.…”
Section: Mr Coronary Vessel Wall Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in a small cohort of healthy volunteers using black‐blood prepared 3D spiral imaging and a highly efficient image based method of respiratory motion compensation has also shown increasing coronary wall thickness with age . This is possibly a precursor of atherosclerosis or it may be part of the normal aging process, or these may be one and the same thing, but the rate of increase in wall thickness observed (0.09 mm per decade) is similar to that observed in autopsy studies.…”
Section: Mr Coronary Vessel Wall Imagingmentioning
confidence: 99%
“…). The reproducibility of this technique has been favorably compared with navigator‐gated imaging and it has demonstrated increasing vessel wall thickness with age in a healthy population . While other techniques with near 100% efficiency have been developed more recently, these have not as yet been applied to imaging the coronary vessel wall where the requirements of respiratory motion control are most stringent.…”
Section: Mr Coronary Vessel Wall Imagingmentioning
confidence: 99%
“…Aging is also characterized by progressive reduction of the physical capacities (Charansonney 2011) of individuals, which is partly due to a decline in cardiac function (Effron et al 1987). Aside from the pathological events such as atherosclerosis and wall thickening (Scott et al 2011) of the large and medium coronary conductance arteries, this can be related to the coronary microvasculature. Indeed, the resistance arteries of the coronary network (arterioles and capillaries) finely regulate the blood flow of the heart, and thus the maximal capacity of that organ to pump blood through the body.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in order to compensate for the age difference between the healthy and the CAD groups, age-adjusted wall thickness values were calculated for the healthy subject group following the results of the previous study by Scott AD et al (47) according to the formula Wa=Wm+0.00880.16667emfalse(Age¯CAD-Age¯Hfalse). Here, Wa, measured in millimeters (mm), is the age-adjusted wall thickness for a healthy subject, Wm (mm) is the measured wall thickness for a healthy subject, and Age¯H and Age¯CAD measured in years, are the average ages of the healthy and CAD subject groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This age difference was inevitable since healthy subjects were chosen based on the absence of known history of CAD and/or risk factors, which is usually affected by age. A prior study by Scott AD et al (47), reported an age-related vessel wall thickening using a vessel wall imaging method at 1.5T in 21 healthy subjects. However, the authors did not correlate this increased with Framingham CAD risk factors such as age >45 years old (6/21) and smoking history (7/21) which was present in their subject population.…”
Section: Limitationsmentioning
confidence: 97%